(untitled) (Philosophy and Progress, 2016)
Learners have to deal with texts they read in many different ways. Some learners comprehend better than others; some take a little while to get to the deeper meanings of the text while some get to the meaning instantly. Some may find it difficult to comprehend even at surface level. Psychologists, linguists and educators have been divided in their opinions about how a young learner comprehends a text and why they are better or worse than their peers in comprehending text. In this article attempts have been made to present a clear definition of what is comprehension; how comprehension happens among readers before, during and after reading; what makes a learner a good or a poor comprehender. While presenting this phenomenon in brief, mentions and citations have been made from established researches /studies in this area along with observations of acknowledged psycholinguists, educators and practitioners. Finally, with support from different studies, an attempt has been made to describe ways and means as to how to improve learners’ reading comprehension. Philosophy and Progress, Vol#53-54; No#1-2; Jan-Dec 2013